PTEN Regulates PI(3,4)P2 Signaling Downstream of Class I PI3K - Malek, Mouhannad; Kielkowska, Anna; Chessa, Tamara; Anderson, Karen E.; Barneda, David; Pir, Pınar; Nakanishi, Hiroki; Eguchi, Satoshi; Koizumi, Atsushi; Sasaki, Junko; Juvin, Véronique; Kiselev, Vladimir Y.; et al. (Elsevier, 2017)
The PI3K signaling pathway regulates cell growth and movement and is heavily mutated in cancer. Class I PI3Ks synthesize the lipid messenger PI(3,4,5)P3. PI(3,4,5)P3 can be dephosphorylated by 3- or 5-phosphatases, the latter producing PI(3,4)P2. The PTEN tumor suppressor is thought to function primarily as a PI(3,4,5)P3 3-phosphatase, limiting activation of this pathway. Here we show that PTEN also functions as a PI(3,4)P2 3-phosphatase, both in vitro and in vivo. PTEN is a major PI(3,4)P2 phosphatase in Mcf10a cytosol, and loss of PTEN and INPP4B, a known PI(3,4)P2 4-phosphatase, leads to synergistic accumulation of PI(3,4)P2, which correlated with increased invadopodia in epidermal growth factor (EGF)-stimulated cells. PTEN deletion increased PI(3,4)P2 levels in a mouse model of prostate cancer, and it inversely correlated with PI(3,4)P2 levels across several EGF-stimulated prostate and breast cancer lines. These results point to a role for PI(3,4)P2 in the phenotype caused by loss-of-function mutations or deletions in PTEN. Malek et al. show that the tumor suppressor PTEN acts as a PI(3,4)P2 3-phosphatase within the growth factor-stimulated PI3K signaling network, in addition to its accepted role as a PI(3,4,5)P3 3-phosphatase. This suggests that specific PI(3,4)P2 effector functions, such as invadopodia formation, play a role in the PTEN-loss-of-function phenotype.
Keywords: cancer; INPP4B; invadopodia; PI(3,4)P2; PI(3,4,5)P3; PI3K; prostate; PTEN; SHIP2